A Meta-ethnography. (June 2015) - Vittner, Dorothy; Casavant, Sharon; McGrath, Jacqueline M.; Ahern, Kathy
<x xml:space="preserve">Abstract</x> Background: Although the benefits of skin-to-skin care (SSC) are well documented in the literature, practices in the clinical setting remain inconsistent. Although nurses' reported knowledge about SSC has improved, confusion still exists regarding safety and appropriateness. Existing qualitative literature primarily focuses on parents' experiences; yet it is crucial to describe the essence of professional caregivers' experiences to enhance facilitation and implementation of SSC. Most studies surrounding the caregiver's perspective and SSC have focused on barriers that impede implementation or examined the experience from the organizational perspective and general group experiences rather than individual personal experiences with SSC. Purpose: This meta-ethnography integrated the findings from several discrete studies into a salient interpretative perspective, creating a relevant understanding of the process of SSC as a means of enhancing facilitation and implementation of SSC with hospitalized infants. Methods: An ethnographic meta-synthesis of qualitative literature was completed. Results: As a result of this synthesis, the caregivers' experiences were separated into themes to articulate the phenomena juxtaposed from the 8 original studies that influence facilitation of SSC for the parent–infant dyad. Qualitative data analysis uncovered 4 overarching themes: (1) varying thresholds of getting started; (2) defining adequate resources; (3) navigating the demands and complexity of the infant; and (4) balancing parental readiness with infant needs. Implications for Practice: This ethnographic meta-synthesis confirms nurses have good intentions in supporting SSC practices, yet struggle to meet competing demands in their daily practice. Implications for Research: Innovative and practical translations of SSC are needed to normalize SSC as the daily standard for premature infants.